Teachers’ Job Satisfaction and Its Influence on Affective Commitment: A Case Study of People's Campus - Shakya, Shreejan; Bajracharya, Rajan Bilas (People's Journal of Management, 2023)
The purpose of this study is to investigate the relationship between teacher job satisfaction and affective commitment of People's Campus. According to the survey method, the data was obtained by a structured questionnaire on a sample of seventy two teachers using a judgmental sampling procedure. Descriptive statistics analysis was employed. All of the independent variables correlated positively and significantly with the dependent variable (affective commitment). If management can target these job satisfaction criteria, it will be easier to generate a commitment among employees to willingly engage in the organization's development.